Does Cholinergic Stimulation Affect the P2X7 Receptor-Mediated Dye Uptake in Mast Cells and Macrophages? - Nurkhametova, Dilyara; Siniavin, Andrei; Streltsova, Maria; Kudryavtsev, Denis; Kudryavtsev, Igor; Giniatullina, Raisa; Tsetlin, Victor; Malm, Tarja; Giniatullin, Rashid (Frontiers in Cellular Neuroscience, 2020)
Background: Extracellular ATP is a powerful trigger of neuroinflammation by activating immune cells via P2X7 receptors. Acetylcholine and nicotinic agonists inhibit ATP-triggered proinflammatory cytokines via the so-called “cholinergic anti-inflammatory pathway” (CAP). However, it remains unclear as to what stage of ATP-induced signaling cholinergic agents provide this anti-inflammatory effect. Using the specific property of P2X7 receptor to open a pathway permeable to large molecules, associated with activation of inflammasome, we studied the action of cholinergic agents on this key event in CAP activation. Methods: Freshly isolated mouse peritoneal mast cells and primary human macrophages were used. To assess P2X7 channel opening, the permeability to the fluorescent dye YO-PRO1 or ethidium bromide (EtBr) was measured by flow cytometry. Expression of nicotinic receptors was probed in macrophages with the fluorescently labeled α-bungarotoxin or with patch-clamp recordings. Results: ATP opened P2X7 ion channels in mast cells and macrophages permeable to YO-PRO1 or EtBr, respectively. This stimulatory effect in mast cells was inhibited by the specific P2X7 antagonist A839977 confirming that YO-PRO1 uptake was mediated via ATP-gated P2X7 ion channels. Cholinergic agents also slightly induced dye uptake to mast cells but not in macrophages, which expressed functional α7 nicotinic receptors. However, both in mast cells and in macrophages, acetylcholine and nicotine failed to inhibit the stimulatory effect of ATP on dye uptake. Conclusion: These data suggest that in immune cells, cholinergic agents do not act on P2X7 receptor-coupled large pore formation but can mediate the anti-inflammatory effect underlying CAP downstream of ATP-driven signaling.